Comparison of Antioxidant and Anti-Inflammatory Effects of Honey and Spirulina platensis with Sulfasalazine and Mesalazine on Acetic Acid-Induced Ulcerative Colitis in Rats - Rezaei, Nadia; Eftekhari, Mohammad Hassan; Tanideh, Nader; Mokhtari, Maral; Bagheri, Zahra (Galen Medical Journal, 2019)
Background: Antioxidant therapy has gained attention for the treatment of ulcerative colitis (UC). The excessive generation of reactive oxygen/nitrogen species in the gastrointestinal tract increases oxidative stress, thereby leading to antioxidant defense depletion, lipid peroxÂidation, inflammation, tissue damage, and ulceration. Spirulina platensis (SP) and honey are excellent sources of potent antioxidants such as polyphenols and other bioactive compounds. We aimed to investigate antioxidant and anti-inflammatory effects of honey and SP in comparison with sulfasalazine (SSZ) and mesalazine on acetic acid-induced colitis (AA-colitis) in rats. Materials and Methods: Fifty-six Sprague Dawley male rats were allocated to seven groups, with each group comprising eight rats. UC was induced, except in normal controls (NC). All groups received oral treatments for seven days. The normal saline solution of 2 mL was intrarectally administered to the NC group. The AA-colitis and NC groups received 2 mL acetic acid intrarectally as a single dose and 2 mL normal saline for seven consecutive days orally. The mesalazine group received 100 mg/kg mesalazine, the SSZ group 360 mg/kg SSZ, the honey or H group 1 mL honey diluted with 1 mL distilled water, the SH group 1g/kg SP and 1 mL honey, and the SP group 1g/kg SP. After clinical activity score assessment, the rats were sacrificed. Colonic weight/length ratio, prostaglandin E2 , myeloperoxidase , nitric oxide , malondialdehyde (MDA), interleukin-1, tumor necrosis factor-Alpha± , interleukin-6 , glutathione peroxidase , total antioxidant capacity , reduced glutathione , and superoxide dismutase were measured. Colonic histopathological changes were observed microscopically.Results: Treatment of UC with SP, honey, and combination regimen significantly reduced TNF-Î±, IL-1Î², IL-6, MDA, MPO, NO, and PGE2, and increased TAC, GSH, GPx, and SOD in interventional groups compared to the AA-colitis group (P<0.05). Conclusion: Honey and SP might be beneficial food supplements for medical nutrition therapy in UC.